Interaksi Kecemasan Matematika dan Self-Efficacy Terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Menengah Pertama - Ragil Ashari; Imam Kusmaryono (Griya Journal of Mathematics Education and Application, 2026)
The purpose of this study is to investigate the influence of math anxiety on creative thinking ability, the influence of self-efficacy on creative thinking ability, and the combined influence of math anxiety and self-efficacy on creative thinking ability in RADEC learning, as well as to investigate the interaction between math anxiety and self-efficacy in their influence on creative thinking ability among 8th-grade students studying linear equations. This study is a quantitative study using an ex-post facto approach. The sample in this study consists of 32 eighth-grade students from Class 8D at SMP Negeri 30 Semarang, selected using cluster random sampling. The instruments used were a mathematics anxiety questionnaire, a self-efficacy questionnaire, and a test of students’ creative thinking ability using linear equation material. Initial data analysis techniques included normality and linearity tests. Hypothesis testing utilized multiple linear regression and two-way ANOVA. The results of the study indicate that: (1) mathematics anxiety and self-efficacy have a simultaneous (joint) effect on students’ creative thinking ability; (2) there is an interaction between mathematics anxiety and self-efficacy in their influence on students’ creative thinking ability;